A new species of Kukri Snake (Oligodon Fitzinger, 1826; Squamata: Colubridae) from the Cat Tien National Park, southern Vietnam - Vassilieva, Anna B.; Geissler, Peter; Galoyan, Eduard A.; Poyarkov, Nikolay Jr A.; van Devender, Robert Wayne; Böhme, Wolfgang (Zootaxa, 2013)
We describe a new species of the genus Oligodon from the lowland forests of Cat Tien National Park, Dong Nai Province, in southern Vietnam. Oligodon cattienensis sp. nov. is distinguished from the remaining Southeast Asian kukri snakes by the combination of the following characters: medium-sized, deeply forked hemipenes without spines, 17-17-15 dorsal scale rows, nasal entire, 2 small postoculars, almost equal in size, 167–178 ventrals, 31–35 subcaudals, 24–35 + 5 large dark-edged vertebral blotches in combination with a yellow-orange or red vertebral stripe between blotches, head pattern including ocular band, temporal bands and elongated chevron, ventrals pink or whitish (reddish in juveniles) in life, some bearing a quadrangular dark blotch on each lateral side, or ventrals being entirely dark. Based on the hemipenial morphology the new species is assigned to the Oligodon cyclurus species group. A comparison table for all Indochinese Oligodon is provided.